Avaliação da competitividade das micro, pequenas e médias empresas de fundição de ferro e/ou aço: survey no mercado brasileiro - Oliveira, Reinaldo José de (2020)
The industry is essential to a country's economic growth. The foundry is considered an important manufacturing process within the industrial sector. Cast parts are used in 90% of all equipment and machines. Brazil occupies the ninth position in the world casting production ranking, however it has lost competitiveness, since it already represented (in 2011) about 3.4% of the world production of castings and currently represents only 2.0%. This research proposed to establish a model for evaluating competitiveness, based on academic literature and experts’ opinion, which could be applied to the MSMEs (micro, small and medium enterprises) in iron and / or steel castings. Also, based on this model, a competitive diagnosis of this segment of the Brazilian foundry sector could be established. This model was tested through a survey of 111 companies within the proposed profile. It was noted that the theoretical model could be applied with results that corroborate the literature on the subject, with regard to the four competitive factors identified, having as theoretical contribution the originality of the study, as the literature lacks a model to analyze the degree of competitiveness of the MSMC iron and / or steel foundry industries. As a result of the survey, a competitiveness ranking could be developed, based on which managers will be able to analyze the competitive positioning of their respective companies and, knowing the competitive elements that influence each factor, will be able to make strategic decisions based on the relevant aspects to competitiveness. The average degree of competitiveness (GE) of the 111 companies was 65%, based on a scale where the maximum value is 100%. Almost half of the companies surveyed have a lower value than this average. The most competitive company has a GE of 94.3% and the least competitive only 18.6%. The two most competitive companies in the ranking are small steel foundries, one of which is in the South and the other in Southeast Brazil.